Is an intertemporal model of the current account valid for East Asian countries? Evidence from structural VAR - Kuo, Chen-Yin (Journal of Business Economics and Management, 2015)
This paper aims to examine the validity of present-value model of current account (PVMCA) by analyzing dynamic responses of variables in PVMCA to structural shocks. In place of the cross-equation restriction tests used in existing research, we adopted a structural vector autoregression framework and obtain three findings. First, evidences from 4 East Asian countries supported the intertemporal theoretical expectation that country-specific transitory shocks significantly affect current accounts, whereas the effects of global and country-specific permanent shocks are negligible. Second, country-specific transitory shocks that primarily affected current account variance dominate net output variation. Third, global permanent and transitory shocks mainly affecting variances in world interest rates and exchange rates secondarily explain current account variance. Therefore, three explanatory variables of PVMCA sufficiently explain current account variations. In practice, investors can use the PVMCA to forecast changes in current accounts; they further judge business risks stemming from the changes, and adjust their security portfolio. First published online: 09 Jun 2015